Exploring Chinese international students’ experiences in the ’Life and Works of Rizal’ course in the Philippines: An interpretative phenomenological analysis - Xu, Xiaoyuan; Castulo, Nilo; Marasigan, Arlyne (Journal of International Students, 2025)
As of 2021, there were 6.4 million international students globally, with Chinese students making up the largest group of international students in the Philippines. This study investigated the lived experiences of Chinese undergraduate international students who took the mandatory Life and Works of the Rizal Course in the General Education Curriculum. The study employed interpretative phenomenological analysis (IPA) with six Chinese undergraduate students. The research findings indicated that Chinese international students recognized the significance of the active participation of local students and a comprehensive cultural environment. In addition, it highlights how Chinese students draw on their cultural heritage and Rizal’s ancestry to gain a deeper understanding of Rizal’s life and work. Students faced challenges, such as language barriers, difficulties with online learning, and a lack of cultural background in the Philippines. Using the ABCs of acculturation theory, the results provide valuable insights into improving students’ experiences in the Rizal course.